Investigation of Two-Dimensional Viscoelastic Fluid with Nonuniform Heat Generation over Permeable Stretching Sheet with Slip Condition - Haroon Ur Rasheed; Zeeshan Khan; Saeed Islam; Ilyas Khan; Juan L. G. Guirao; Waris Khan (Complexity)
Here, in this research article, we have investigated an incompressible viscoelastic fluid flow over a uniform stretching surface sheet along with slip boundary conditions in the presence of porous media. The partial differential equations which govern the fluid flow are changed into ordinary differential equations through suitable similarity transformation variables. Finally, the transformed ordinary differential equations are solved with the help of a seminumerical technique known as the homotopy analysis method (HAM). The uniqueness of our study is not only to analyze and carry out the effect of the elastic parameter but also to account for viscous dissipation which is important in the case of optically transparent flow. The novel effects for the parameters which affect the flow and heat transfer, such as the Eckert number, porous medium parameter, and the velocity slip parameter, are studied through graphs. Also, the convergence analysis for the proposed method is addressed. Additionally, for the sake of validation, the present work is also compared with the already published work and an outstanding agreement is found.